Comparing psychiatric routine care and integrative psychiatry – A study protocol for a prospective observational study (INTEGRAL). Issue 1 (March 2023) - Rezo, A.; Wagner, P.; Sanchez, A.; Brunnhuber, S.; Pedrosa Gil, F.; Rapp, M.A.
Abstract: Introduction: In recent years, complementary and alternative medicine therapies have been increasingly studied for their effectiveness, and there are more and more studies supporting the use of some practices in the psychiatric setting. Despite the high acceptability and interest of patients using a holistic approach to recover from mental health issues, complementary and alternative medicine therapies are not yet integrated in the conventional treatment. This study investigates the potential of an integrative psychiatry approach compared to treatment as usual in a heterogeneous inpatient population. Methods: INTEGRAL is an observational study comparing two psychiatric hospitals. In total 240 inpatients with a diagnosis of a mental disorder (substance use, schizophrenia, depression, anxiety, post-traumatic stress and somatoform disorder) will be included. One hospital offers standard therapy, the other one has established an integrative medicine approach combining conventional treatment with CAM. The integrative approach provides a non-standardized complex patient-centered mental health care. Outcomes will be assessed at three time points and focus on the following three frameworks: severity of disease, personal recovery and trans-diagnostic phenomena. Discussion: To our knowledge and research, this study is the first prospective observational study comparing psychiatric routine care and integrative psychiatry and will give us a glimpse of the effects on severity of disorders, trans-diagnostic symptoms and recovery in different psychiatric inpatient populations in the short and long term. The study may help to optimize the treatment of patients suffering from severe mental illness in providing a patient-centered approach with a diversity of evidence-based practices.